Prevalence and incidence rate of hospital admissions related to medication between 2008 and 2013 in The Netherlands. Issue 12 (13th October 2020) - Lghoul‐Oulad Saïd, Fouzia; Hek, Karin; Flinterman, Linda E; Herings, Ron MC; Warlé‐van Herwaarden, Margaretha F; de Bie, Sandra; Valkhoff, Vera E; Alsma, Jelmer; Mosseveld, Mees; Vanrolleghem, Ann M; Stricker, Bruno HCH; Sturkenboom, Miriam CJM; et al.
Abstract: Purpose: In 2009 a Dutch guideline was published containing recommendations to reduce Hospital Admissions Related to Medications (HARMs). This study aims to examine time‐trends of HARMs and their potential preventability between 2008 and 2013 in The Netherlands. Methods: A retrospective prevalence study was conducted using the Dutch PHARMO Database Network. A semi‐automated pre‐selection was used to make a crude identification of possible HARMs of which four samples were selected. These were independently assessed with respect to causality and potential preventability by a physician and pharmacist. The results were stratified by age into 18‐64 years and 65 years and older. For these groups the net prevalences and incidence rates of HARMs and potentially preventable HARMs were calculated for the years 2008, 2009, 2011 and 2013. Results: Four samples of 467 (2008), 447 (2009), 446 (2011) and 408 (2013) admissions were assessed. The net prevalence of HARMs in the 18‐64 years group was approximately four times smaller compared to the older group with a mean prevalence of 2.7% (95% confidence interval [CI]:2.4%‐3.0%) and 10.2% (95%CI: 9.7%‐10.7%) respectively. The potential preventability was 25.1% (18.4%‐31.8%) and 48.3% (95%CI: 44.8%‐51.8%), respectively. The prevalence of HARMs in both groups did not change significantly between 2008 and 2013 with 2.4% (95%CI: 1.9%‐3.0%) and 10.0% (95%CI: 9.0%‐11.0%) in 2008 and 3.1% (2.7%‐3.5%) and 10.4% (95%CI: 9.4%‐11.4%) in 2013, respectively. Conclusion: Despite efforts to reduce HARMs, the prevalence did not decrease over time. Additional measures are therefore necessary, especially in the elderly population.